Association of drinking water and migraine headache severity. (July 2020) - Khorsha, Faezeh; Mirzababaei, Atieh; Togha, Mansoureh; Mirzaei, Khadijeh
Highlights: Negative correlation between water intake and visual analog scale. Negative correlation between water intake and migraine severity. Negative correlation between water intake and frequency of headache. Negative correlation between water intake and duration of headache. Positive correlation between tea and migraine severity. Abstract: Objectives: Migraine is a common type of headaches and disabling disorder. Based on evidences dehydration is closely related to promote migraine headcahe frequency and severity. The Water intake is the best intervention to reduce or prevent headache pain. water intake in migraine patients has rarely been studied. the present study aimed to evaluate the relation between water intake and headache properties in migraine. Methods and materials: The present study was conducted using a cross-sectional design on 256 women 18–45 years old referred to neurology clinics for the first time. The diagnosis of migraine by a neurologist the according to ICHD3 criteria and To assess migraine severity the Migraine disability assessment questionnaire (MIDAS), visual analog scale (VAS), and a 30-day headache diary were used. One-way analysis was used to evaluate the associations between MIDAS and VAS with daily water intake. Pearson correlation analysis was used to evaluate the relationship between the number of days and duration of headache with daily water intake. Data were analyzed using SPSS software and P-values < 0.05 considered statistically significant. Results: The results showed that the severity of migraine disability (P < 0.001), pain severity (P < 0.001), headaches frequency (P < 0.001), and duration of headaches (P < 0.001) were significantly lower in those who consumed more water or total water. Conclusion: The present study found a significant negative correlation between daily water intake and migraine headache characteristics but further clinical trials are needed to interpret the causal relationship.